1.ASYMMETRIC DIMETHYL ARGININE AND UROMODULININ THE CHRONIC KIDNEY DISEASE (Iraqi Journal of Medical Sciences, 2020)
Asymmetric dimethyl arginine, symmetric dimethyl arginine and uromodulin used as early biomarkers of diagnosis renal diseases. The early stages side effects of inveterate kidney malady are ordinarily not clear. Noteworthy decrease of the kidney work is the primary self-evident sign of infection. On the off chance that analyzed early stages 1 to 3, the movement of unremitting kidney infection can be changed and complications diminished. In stages 4 and 5 broad kidney harm is watched, which as a rule comes about in end-stage renal disappointment.Keywords:Symmetric Dimethyl arginine, uromodulin and kidneyCitation:Ali NM. Asymmetric dimethyl arginine and uromodulin in the chronic kidney disease. Iraqi JMS. 2019; 17(3&4): 166-167. doi: 10.22578/IJMS.17.3&4.1
Keywords: Symmetric Dimethyl arginine; uromodulin and kidney